Cell-autonomous cytokinin-independent growth of tobacco cells transformed by Agrobacterium tumefaciens strains lacking the cytokinin biosynthesis gene. - Black, R C (1994)
Mutations at the cytokinin biosynthesis locus (tmr) of Agrobacterium tumefaciens usually result in strains that induce tumors exhibiting the rooty phenotype associated with high auxin-to-cytokinin ratios. However, tobacco (Nicotiana tabacum cv Havana 425) leaf disc explants responded to tmr- mutant strain A356 by producing rapidly growing, unorganized tumors, indicating that these lines can grow in a cytokinin-independent fashion despite the absence of a functional tmr gene. Several methods have been used to characterize the physiological and cellular basis of this phenotype. The results indicate that tmr- tumors have a physiologically distinct mechanism for cytokinin-independent growth in comparison to tumors induced by wild-type bacteria. The cytokinin-independent phenotype of the tmr- transformants appears to be cell autonomous in nature: only the transformed cells and their progeny were capable of cytokinin-independent growth. Specifically, the tmr- tumors did not accumulate cytokinin, and clonal analysis indicated the tmr- transformed cells were not capable of stimulating the growth of neighboring nontransformed cells. Finally, the cytokinin-independent phenotype of the tmr- transformants was shown to be cold sensitive, whereas the wild-type tumors exhibited a cold-resistant cytokinin-independent phenotype. Potential mechanisms for this novel form of cytokinin-independent growth, including the role of the dehydrodiconiferyl alcohol glucosides found in both tumor types, are discussed.